Paving The Way For International Cooperation: Policy Urgency The Law Of Intercountry Transfer Of Prisoners In Indonesia - Soge, Markus Marselinus; Priyatmono, Budi (Jurnal Hukum dan Keadilan, 2024)
The lack of regulations on the transfer of prisoners between countries in Indonesia is an obstacle to establishing international cooperation on this matter. The large number of Indonesian citizens who are imprisoned abroad and need legal protection is an important reason for Indonesia to resolve this issue. The absence of regulations on the transfer of prisoners between countries needs to be addressed immediately to ensure legal protection for Indonesian citizens imprisoned at home and abroad. This research aims to study the extradition process in Indonesia and the importance of legal protection for Indonesian citizens imprisoned abroad for committing criminal offenses. The results obtained are that government efforts to protect Indonesian citizens abroad have been made, but need to be improved by strengthening coordination, increasing resources, and establishing international cooperation.